The relationship between serum oestradiol concentration and energy balance in young women distance runners - Zanker, C. L.; Swaine, I. L. (International Journal of Sports Medicine, 1998)
Reproductive dysfunction in women distance runners has been linked to an imbalance between energy intake (EI) and energy expenditure (EE) which leads to an energy deficit. To determine whether ovarian suppression is associated with an energy deficit, the relationships between serum oestradiol (E2) concentration and indices of energy balance (EB) were explored in a group of women runners with a variety of menstrual patterns and a range of activity levels. Subjects comprised 33 women distance runners of mean (SD) age 27.2 (1.8) years. Sixteen of these women were defined as eumenorrhoeic (11-13 menstrual bleeds per year during the past 2 years), 8 as oligomenorrhoeic (< or = 3 menstrual bleeds per year for 2 years) and 9 as amenorrhoeic (absence of menses for > 1 year). Their volume of running training ranged from 36 to 97 km x wk(-1) [mean (SD): 68.6 (21.4) km x wk(-1). The body mass index (BMI) and percent body fat (BF) of each subject was measured. Their mean daily energy balance (EB) was calculated by subtracting their dietary EI from their estimated EE recorded over 7 days. Serum concentrations of E2, total T3 and IGF-1 were measured from a fasting blood sample (taken in early follicular phase for Eu women). Relationships between serum E2, T3 and IGF-1, EB, BMI and BF were explored using bivariate correlation and regression analysis. The results showed that the most powerful predictors of serum E2 concentration were estimated EB (r = 0.88, P<0.001), serum T3 (r=0.94, P<0.001) and IGF-1 (r=0.84; P<0.001). Weaker correlations were observed between serum E2 and BMI (r=0.42; P=0.008) and serum E2 and BF (r=0.48; P=0.004). These relationships add support to the hypothesis that reproductive dysfunction in women distance runners is associated with an energy deficit.